Stakeholder understandings of the Human Papillomavirus (HPV) vaccine in Sub-Saharan Africa: a qualitative systematic review - Deignan, Caroline (Department of Public Health and Family Medicine, 2020)
Cervical cancer rates in Sub-Saharan Africa (SSA) are amongst the highest in the world. The World Health Organization currently estimates that worldwide, cervical cancer will kill more than 443,000 women per year by 2030, of which 90% of deaths are predicted to occur in SSA. The Human Papillomavirus (HPV) vaccine provides primary protection against the most common cancer-causing strains of HPV that are responsible for cervical cancer. Over the last five years, there has been a slow increase in the number of African countries that have introduced the HPV vaccine via demonstration and pilot projects, and a minority of African countries that have incorporated the HPV vaccine into their National Immunisation Programmes. As part of this systematic review, a literature review was conducted and revealed that research has been conducted on top-down barriers and facilitators to HPV vaccine uptake and have found that poor health system capabilities, inaccessibility to medical care, low cervical cancer screening levels, inadequate infrastructure, finances, and health worker training are significant systemic barriers to HPV vaccination success in SSA. Little research has been conducted on demand-side or end-user perspectives of, and decisions around, the HPV vaccine. In order to complement existing research, and inform current and future implementation approaches, this qualitative systematic review explored stakeholder understandings of the HPV vaccine in SSA. This review searched the following databases: Embase (via Scopus), Scopus, MEDLINE (via PubMed), PubMed, EBSCOhost, Academic Search Premier, Africa-Wide Information, CINAHL, PsycARTICLES, PsycINFO, SocINDEX, Web of Science, and the Cochrane Controlled Register of Trials (CENTRAL) and found a total of 259 articles. Of these, 31 articles met the inclusion and exclusion criteria and were included in the review. Braun and Clarke’s six step process for conducting a thematic analysis was used for analysis and studies were assessed for quality using the Critical Appraisal Skills Programme (CASP) checklist. Three major themes emerged from the thematic analysis: knowledge is intertwined with misinformation; fear shapes contradictory perceptions about the HPV vaccine; and social norms and gender dynamics are relevant factors in how stakeholders understand the HPV vaccine in SSA. This review iterates the importance of first working with communities to gauge understandings of the HPV vaccine, before trying to implement change through education, sensitization and behavior change.